Consolidation of Media Markets in the European Union : State of the markets and the role of merger control - Äijälä, Laura (My University, 2019)
The subject of the thesis is the concentration of ownership of media and electronic communications sectors primarily from competition law standpoint. For the purpose of this study, the ‘media sector’ refers to so called mass media, comprising for instance the press and television industries. The focus of research is on audiovisual media. Technological development, digitalisation and convergence have in recent year had a remarkable impact on the operation and market structure of mass media markets. Additionally, many undertakings traditionally active in electronic communication services and technology sector have ventured into media content businesses. The current state of the market seems to favour large units over their smaller counterparts. This is also evident in relation to the European Union merger control, as the EU competition authorities have during the past decade received numerous notifications of concentrations such as mergers, acquisitions and joint ventures between media and telecommunications providers. The purpose of this study is to first find out what is the current state and structure of the European Union mass media markets. Following that, the aim is to map out the essential competitive issues media consolidation development may generate as well as consider what are its implications towards media plurality in Europe. The legislative and policy initiatives set out in the EU Digital Single Market strategy and potential efficiencies brought about by media concentration are also briefly revisited.
Keywords: eurooppaoikeus, kilpailuoikeus, media-ala, joukkoviestintä, yrityskaupat, keskittyminen